The Influence of Student Consumption, Social Status of Family,The Economic Parent Status, and The Economic Education of Family to Consumption Behavior - Mulyani, Rinna; Thomas, Partono; Widiyanto, Widiyanto (Universitas Negeri Semarang, 2018)
Consumption Behavior Consumptive students due to the knowledge of consumption and the lack of parental role in modeling and low family economic education in providing education about consumption of their children led to consumptive behavior. The formulation of this problem is whether there is influence of students' consumption knowledge, family's economic social status, family economic education on consumption behavior of high school students.The variables in this research are Knowledge of Student Consumption, Parents Social Economic Status, Family Economic Education, and Student Consumption Behavior. The method used is data analysis with data collection techniques Student population of SMA Negeri IPS Class XII. Sample of the research amounted to 191 respondents with sampling technique using Proportional Random Sampling. Methods of data collection using questionnaires. Data analysis with Linear Regression.The result of research there is influence of student's consumption knowledge, socio-economic status of family, and family economic education either partially or simultaneously. Based on t test, the influence of students' consumption knowledge on the partial consumption behavior of students obtained value of 7.239, the influence of socioeconomic status of parents to student consumption behavior 3.852 and the influence of family economic education on student consumption behavior of 1.686. Simultaneously influence of knowledge of student consumption, parent economic ststus, family economic education to student consumption behavior based on F test obtained value 30, 375.